Compatible blending for circular textiles with next-gen materials - Forst, Dr Laetitia; Goldsworthy, Prof. Kate (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Emerging next-gen materials such as recycled, renewable, or regenerative fibres promise lower impacts in resource extraction and transformation processes than their conventional fibre counterparts. These materials can be instrumental in a shift to a more sustainable fashion and textiles industry. A key contribution to this transition relies on reducing impacts and waste through circular design measures such as increasing lifespans and recycling at end of life. However, as these next-gen materials tend to have properties and costs that deviate from optimised industry norms, they are often used in incompatible blends, thus negating their circularity potential. This paper puts forward a framework to understand material flows and lifecycles as a relation between fibre type and recycling route for designers to operate within the principles of circularity. The research results in a guidebook to support designer’s choices of material combinations in line with recycling trajectories, and in a series of samples produced by industry project partners and students demonstrating the application of the framework. The samples use a selection of five example next-gen materials, which are integrated to each practitioners’ applications and aesthetics. The underlying aim of the research is to foster a systemic approach to textile design with an increased understanding of material properties and their relation to current and emerging recycling technologies.